Evaluasi Implementasi Sistem Informasi Manajemen Berbasis Teknologi Cloud Computing pada Usaha Kecil dan Menengah (UKM) - Silvi Rahmawati; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
The implementation of management information systems based on cloud computing technology has become a topic of interest in the context of small and medium-sized enterprises. This article aims to evaluate the implementation of management information systems based on cloud computing technology in small and medium-sized enterprises, highlighting the associated benefits, challenges and opportunities. Through a literature review, we identify the experiences of small and medium-sized enterprises that have adopted cloud-based management information systems and their impact on operational efficiency, flexibility, data security, and competitive advantage. We also considered factors that influence implementation success, such as cost, technical expertise, and organizational readiness. By conducting this evaluation of cloud computing information systems, it is expected to identify problems that hinder the implementation of cloud computing in small and medium-sized enterprises. The article concludes by providing practical advice for small and medium-sized enterprises that are considering or are in the process of implementing cloud-based management information systems, as well as providing guidance for further research in this area.